Facies Architecture and Sedimentological Controls as Indicators of Reservoir Potential in The Tidally Influenced Fluvial–Estuarine Deposits Within the Frontier Anambra Basin, Southeastern Nigeria. (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Comprehensive sedimentological investigations of the Awkuzu outcrops within the frontier part of the Anambra Basin, southeastern Nigeria, reveal two major facies associations: (i) fluvial/tidally influenced fluvial facies and (ii) estuarine facies. These facies correspond to the Eocene Nanka Formation, deposited in a tidally influenced fluvial–estuarine system characterized by alternating high- and low-energy depositional regimes. Integration of field observations, paleocurrent measurements, ichnological evidence, and pebble morphometric analyses provides insights into the facies architecture, depositional processes, and reservoir potential.The fluvial/tidally influenced fluvial facies comprises medium- to coarse-grained, moderately sorted sandstones and conglomeritic beds arranged in multistoried, fining-upward successions. Sedimentary structures such as planar and trough cross-bedding, erosional channel bases, and mud drapes suggest deposition under high-energy fluvial conditions intermittently modified by tidal currents. Trace fossils including Ophiomorpha, Planolites, and Arenicolites indicate episodic marine influence. Pebble morphometry shows Maximum Projection Sphericity (MPS) values of 0.76–0.85, Flatness Index (FI) of 58–67%, and OPI ranging from –0.12 to +0.18, denoting moderately high sphericity and rounding typical of sustained fluvial transport with limited tidal reworking. These features point to excellent reservoir potential, enhanced by high porosity, permeability, and lateral sand continuity.The estuarine facies comprises heterolithic and laminated fine- to medium-grained sandstones, siltstones, and claystones displaying flaser, wavy, and lenticular bedding indicative of tidal cyclicity. Skolithos and Planolites ichnofabrics reflect deposition in a well-oxygenated, shallow marine to inner estuarine setting. Pebble morphometry results (MPS: 0.68–0.77; FI: 70–80%; OPI: predominantly negative) indicate moderate sphericity and sub-rounded, oblate shapes, characteristic of low-energy, oscillatory tidal currents with limited abrasion. Although reservoir quality is reduced by mudstone intercalations, lateral sand continuity supports potential fluid connectivity.Overall, the facies architecture demonstrates that sedimentological controls and depositional energy variations fundamentally influence reservoir heterogeneity and quality within the tidally influenced fluvial–estuarine deposits of the Nanka Formation in the Frontier Anambra Basin.